1995
DOI: 10.1177/001440299506100405
|View full text |Cite
|
Sign up to set email alerts
|

Communication versus Compliance: African-American Parents' Involvement in Special Education

Abstract: A longitudinal, 3-year study investigated the participation of African-American parents of 24 preschoolers in special education programs in a large urban school district. Data were collected through ethnographic interviews with parents and professionals, observations of conferences, and examination of students' documents. Despite current perceptions of low levels of participation by African-American parents, the data show consistent initial efforts by families to support their children's schooling, eventually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
2
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 13 publications
5
129
2
2
Order By: Relevance
“…Finally, logistical issues can present challenges, particularly for low-income families. Schools may schedule meetings at short notice and at times difficult for parents to attend (Linan-Thompson & Jean, 1997;Harry, Allen & McLaughlin, 1995), particularly for lower income families with less ability to change work schedules (Lareau & Shumar, 1996). Reading level of materials sent to parents may not be appropriate and comprehensible (Harry, 1992;Leung, 1996;LinanThompson & Jean, 1997), particularly when non-English speaking parents are sent materials in English only (Weiss & Coyne, 1997).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, logistical issues can present challenges, particularly for low-income families. Schools may schedule meetings at short notice and at times difficult for parents to attend (Linan-Thompson & Jean, 1997;Harry, Allen & McLaughlin, 1995), particularly for lower income families with less ability to change work schedules (Lareau & Shumar, 1996). Reading level of materials sent to parents may not be appropriate and comprehensible (Harry, 1992;Leung, 1996;LinanThompson & Jean, 1997), particularly when non-English speaking parents are sent materials in English only (Weiss & Coyne, 1997).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Reading level of materials sent to parents may not be appropriate and comprehensible (Harry, 1992;Leung, 1996;LinanThompson & Jean, 1997), particularly when non-English speaking parents are sent materials in English only (Weiss & Coyne, 1997). Behavior of professionals may also serve as logistical deterrents to advocacy, including limited time for conferences; emphasis on documents rather than participation; and use of professional jargon (Harry, Allen & McLaughlin, 1995).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Several authors have conducted studies on parents of children with disabilities to better gain an understanding of the level of their involvement with their children's education, their perceptions of the children and their views on the school system (Harry, 1992a;1992b;Harry et al 1995;Harry et al, 1999). These studies overall concluded that: (a) parents mistrusted school personnel, (b) parents felt that the school setting was cold and uncaring towards them, (c) parents deferred decisions to school personnel even when they did not agree with those decisions, (d) parents felt overwhelmed by all the written communication they received regularly from school personnel regarding their children, (e) culture had a strong influence on parental perceptions of children, (f) engagement with school personnel was limited to a large degree by language barriers and to a small degree by cultural differences, (g) parental involvement decreased over time because parents had limited understanding of the structures, guidelines and procedures of IDEA, (h) professionals had limited understanding of the minor nuances within a group's cultural and ethnic beliefs, and therefore, failed to engage them appropriately, and (i) parental involvement was strongly influenced by values, beliefs, customs and conceptual knowledge that were closely aligned with culture and acculturation.…”
Section: Methodsmentioning
confidence: 99%
“…The parents were described as being limited in their abilities to participate fully in the process by school personnel. Harry et al (1995) described a system marred by rigid structures, guidelines and procedures that was inflexible to the needs of CLD parents of children with disabilities and their daily challenges.…”
Section: Culturally and Linguistically Diverse Communitiesmentioning
confidence: 99%
See 1 more Smart Citation